A multiphysics-multiscale-multidrive theoretical model for C₃S hydration - Liu, Yang (2023)
A multiphysics-multiscale-multidrive model for C3S hydration is developed theoretically in this paper. Firstly, the governing equations are formulated with thermo-chemo-electrical coupled fields during C3S hydration, including Nernst-Planck equation for ionic diffusion and chemical reaction, conduction equation for heat transfer, and Poisson equation for electrical field. Secondly, the multiscale computations are achieved from the ionic concentrations, electric potential and C–S–H nuclei number at micro-scale level to the heat flow, chemical shrinkage and C–S–H density at macro-scale level. Thirdly, the multidrives (C3S dissolution, both C–S–H and CH precipitation, the gradients of ionic concentration, electric potential and chemical activity) are included for physiochemical reactions. In addition, the full process of hydration heat flow and chemical shrinkage is integrated and formulated theoretically during all the five periods. After validation with experimental results, it is confirmed that the present model can characterize well the time evolution of the hydration heat flow, chemical shrinkage, and ionic concentrations. Moreover, the effects of water-to-cement ratios (w/c) and specific surface areas on C3S hydration kinetics are investigated by the model, indicating that (a) the drastic increase of initial silicate concentration is captured theoretically, (b) the slight influence of w/c on hydration kinetics is confirmed by the model.